Star trek. Strange new worlds. Season one [videorecording (DVD)] - Goldsman, Akiva; Kurtzman, Alex; Lumet, Jenny, 1967-; Roddenberry, Gene (CBS, 2023)
Season One is based on the years Captain Christopher Pike manned the helm of the U.S.S. Enterprise. The series features fan favorites from Season Two of STAR TREK: DISCOVERY: Anson Mount as Captain Christopher Pike, Rebecca Romijn as Number One, and Ethan Peck as Science Officer Spock. The series follows Captain Pike and the crew in the decade before Captain Kirk boarded the U.S.S. Enterprise, as they explore new worlds around the galaxy.